Kinematics Analysis of a 5-DOF Manipulator - Fu Guodong; Zheng Xiangzhou; Huang Si (Jixie chuandong)
Aiming at a designed W- 5D type underwater sampling manipulator,the parameters and forward kinematics model is established by using the D- H method. According to the structural characteristics of the adjacent 3 joints with parallel axes of the manipulator,by a geometrical method is introduced based on the method of separation of variables,the inverse kinematics closed solution is obtained,whose structure is concise and easy to operate,the requirement of manipulator in the operating environment of underwater is meet,and the basis for the manipulator motion planning and trajectory control is provided. The simulation model of the manipulator is established by MATLAB Robotics Toolbox. The toolbox ikine function is an important method to get the inverse solution of industrial robot,by comparing with the results from the ikine function the superiority and feasibility of the closed solution is verified.